Pengaruh Partisipasi Anggota Dan Pelayanan Kredit Terhadap Keberhasilan Koperasi Pegawai Repubik Indonesia (Kpri) Tugu Lilin Pajang Surakarta - Pamungkas, Aldita Yoga, Fauzan, SE, Ak, M.Si (2016)
Cooperatives is a association of person or law agency in which the object to the well-being of together and in an association of they contain azaz family mutually worked together to and please help of the members of the cooperative.Hence, the success of cooperatives very important for economic growth rate indonesian. This study aims to to analyze the influence of members participation and credit services to successful in cooperatives employees of the republic of indonesia tugu wax lengths surakarta.Population this research is the members of the cooperative employees of the republic of indonesia tugu wax lengths surakarta.Sample selection was conducted using insendential sampling.Research sample areas 48.The method of analysis the data used was regression analysis linear multiple. The result of this research show that the two independent variable namely members participation and credit services influential and significant to successful cooperatives.